Nikah Beda Agama Perspektif al-Manar - Saifullah Saifullah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2008)
This study aims to examine the interpretation of al-Manar on interfaith marriage, especially between Muslims and non-Muslims. Using a qualitative method and a literature study approach, this study traces Rashid Ridha's interpretation in Tafsir al-Manar of verses from the Qur'an relating to interfaith marriage, such as Surah al-Baqarah: 221 and QS. al-Ma'idah: 5. The results show that al-Manar provides a more contextual and moderate view, allowing marriage between Muslim men and Ahlul Kitab women under certain conditions, but still rejecting the marriage of Muslim women to non-Muslim men. This interpretation reflects a reformist approach that considers social realities and the principle of benefit. This study confirms that the interpretation of al-Manar tries to balance between normative texts and social contexts in matters of Islamic family law.